Implementasi Urban Farming Berbasis Energi Terbarukan Menggunakan Sistem Hidroponik di BUMG Pelita Jaya Gampong Barabung - Riski Arifin; T. Arriessa Sukhairi; Arief Gunawan; Syaubari; Rika Sri Utami; Nur Irhamni Sabrina; Dhea Nur Fadhilah; Okpri Meila (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
Gampong Barabung, Aceh Besar Regency, has considerable agricultural potential, but the application of modern agricultural technology is still relatively limited. This activity aims to design, build, and implement a solar-based hydroponic system as an alternative to sustainable plant cultivation at the village level. The implementation method includes location surveys, hydroponic installations, solar system installations, and assistance and system evaluation. The results of the activity show that an NFT hydroponic system with a capacity of 120 planting holes has been successfully built which is directly integrated with a solar panel with a capacity of 150 Wp as an energy source for a nutrient circulation pump. The system built can operate well and be used for vegetable cultivation. The results of the implementation show that the integration of hydroponic technology and solar energy can be applied well and has the potential to support more efficient and environmentally friendly agricultural practices at the village level.